2022
DOI: 10.3844/ajavsp.2022.219.227
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Pre-Weaning Growth of Crossbred between Belgian Blue and Wagyu Bulls with Brahman Cross Dams

Abstract: This study was conducted to observe characteristics and preweaning growth traits of calves born from crossbreeding between Wagyu and Belgian Blue (BB) bulls with Brahman Cross (BX) dams. The experiment was conducted to compare two different crosses Belgian Blue (BB) x BX, Wagyu x BX and also with BX pure breed (BX x BX). In the first two crosses, we used Artificial Insemination (AI), while in the third natural mating occurred. The number of calves in the experiment was 18 from the first cross (BB-crossed), 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The maternal genetic effect influenced the performance of growth traits of the preweaning calf (Lopes et al 2013). Panjono et al (2022) reported that during the pre-weaning period, maternal genetics was related to the growth of calf. The mothering ability was closely related to the maternal genetic traits of the cows that affect milk production and suckling behavior.…”
Section: Effect Of Breed On Cow Performance During Lactationmentioning
confidence: 99%
“…The maternal genetic effect influenced the performance of growth traits of the preweaning calf (Lopes et al 2013). Panjono et al (2022) reported that during the pre-weaning period, maternal genetics was related to the growth of calf. The mothering ability was closely related to the maternal genetic traits of the cows that affect milk production and suckling behavior.…”
Section: Effect Of Breed On Cow Performance During Lactationmentioning
confidence: 99%
“…This cattle has an 11-nucleotide base deletion in the myostatin gene. In Indonesia, these cattle were bred by crossbreeding with other Bos taurus or local Indonesian cattle [ 1 , 2 ]. The Belgian Blue cannot adapt well to warm regions; therefore, the BB is crossed with other local cattle, one of which is the Friesian Holstein (FH), resulting in better performance than other crossbreds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%